Productivity factors of the Finnish semi-domesticated reindeer (Rangifer t.tarandus) stock during the 1990s - Jouko Kumpula; Alfred Colpaert; Mauri Nieminen (Rangifer, 2002)
Intensive reindeer grazing and the increase of other land use forms have caused a decline in the amount of arboreal (Alectoria, Bryoria spp.) and reindeer (Cladina spp.) lichens in the Finnish reindeer management area during the last few decades. Supplementary feeding of reindeer has increasingly compensated for the lack of natural winter fodder. The amount of the supplementary feeding and the quantity and quality of summer pastures should therefore have an increasing effect on the productivity of reindeer stock. In order to outline better the present carrying capacity problems on pastures in the Finnish reindeer management area we focused some of the most important productivity factors of Finnish reindeer stock from 1993 to 1999. The results showed that the productivity of reindeer stock in Finland was dependent especially on two main elements: amount of reindeer feeding and reindeer densities on summer pastures. Winter pastures had no clear effect on productivity when analysing the entire management area. High productivity figures in reindeer stock (calf production, carcass mass and meat production per reindeer) were reached in the management districts where winter feeding was the most abundant, reindeer densities relatively low and summer pastures abundant. An increase in reindeer density on summer pastures raised meat production per total summer pasture area but decreased carcass mass of reindeer calves and meat production per reindeer. It seems that the fundamental factor for keeping the reindeer stock productivity sustainable at a high enough level is to optimize the longterm reindeer densities on pastures. Summer pastures may gradually become a limiting factor for reindeer stock productivity in some areas if overgrazed and decreased winter pastures are only compensated for by winter feeding of reindeer.